PERSPECTIVES OF IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE TOOLS IN RESEARCHING COUPS D’ÉTAT - Kazić, Tanja (The Policy of National Security, 2023)
The study of coups d’état emerged and reached its peak during the second half of the 20th century, coinciding with the global Cold War and centering around examination of coup activities occurring predominantly in African, Asian, Middle Eastern and Latin American countries. This interest was predominantly focused of description of the phenomenon, as well as on the search for its root causes and results. As the Cold War ended, so did the interest for coups started to diminish, and some researchers even dared to pronounce this phenomenon a thing of the past, due to global promotion of respect of national sovereignty and integrity and implementation of democratic practices. However, this phenomenon persisted and re-emerged in the beginning 21st century, especially on the African continent, only to escalate with the time passing by, and reach its Cold War tempo by the beginning of the second decade of the century. Having the renewed interest for coup study in mind, the author will present the current practices in the study of coups d’état, as well as examine the possibilities of using artificial intelligence-assisted tools in the service of operationalization and perfecting the study of political violence, with the goal of introducing new methods of research into the field. With the use of content analysis, as well as theoretical examination of benefits offered by the omnipresent artificial intelligence-assisted tools, the author will provide an answer to the following research question: Which artificial intelligence-assisted tools can improve the study of coups, and in what way?
Keywords: coup d’état; political violence; artificial intelligence; machine learning; statistics; predictive analytics